2022
DOI: 10.3390/ijerph191912173
|View full text |Cite
|
Sign up to set email alerts
|

Certain Dietary Nutrients Reduce the Risk of Eye Affliction/Retinopathy in Individuals with Diabetes: National Health and Nutrition Examination Survey, 2003–2018

Abstract: As the global trend of diabetes intensifies, the burden of vision-threatening retinopathy, particularly diabetic retinopathy (DR), is increasing. There is an urgent need to seek strategies for early prevention and control of DR. This study attempted to comprehensively evaluate the relationship between dietary nutrient intake and the risk of DR to provide assistance for doctors in guiding the diet of diabetic patients. Data from eligible participants with diabetes from the US National Health and Nutrition Exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Four cross-sectional studies were included in this systematic review. Zhang et al used the NHANES database to conduct a cross-sectional study about the association between copper intake and the risk of diabetes nephropathy [ 20 ]. There were no significant differences between either group in term of hypertension or lipid profile.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four cross-sectional studies were included in this systematic review. Zhang et al used the NHANES database to conduct a cross-sectional study about the association between copper intake and the risk of diabetes nephropathy [ 20 ]. There were no significant differences between either group in term of hypertension or lipid profile.…”
Section: Resultsmentioning
confidence: 99%
“…There were no significant differences between either group in term of hypertension or lipid profile. The study showed that as the intake of copper increases, the risk for diabetes nephropathy decreases, with a pooled odds ratio of 0.67 (95% CI: 0.54–0.84) [ 20 ]. A second cross-sectional study by Tan et al into 128 overweight and obese Malaysian adults tested the association between dietary copper intake and insulin resistance [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, further studies are required to confirm this proposal for identifying a precise understanding regarding this point. Furthermore, dietary fiber presented in the functional soup may also play a role [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber intake, particularly soluble fiber, decreases the risk of dementia [ 19 ]. Dietary fiber improves not only cognition but also eye health [ 20 , 21 ]. It has been demonstrated that dietary fiber modulates the gut microbiome giving rise to the improvement of cognition, and eye dryness [ 17 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary fiber manifests an inhibitory impact on the kinetics of monosaccharides and fatty acid digestion and absorption, impeding their prompt assimilation, thereby reducing calorie absorption [181]. The utilization of this therapeutic approach demonstrated a reduction in the likelihood of DR [182]and has a protective effect against existing cases [99]. Investigations have elucidated that individuals with low dietary fiber intake have a higher risk of vision-threatening DR [183].…”
Section: Dietary Fibermentioning
confidence: 99%